Pengaruh Kecerdasan Emosional Dan Lingkungan Kerja Terhadap Kinerja Anggota Kepolisian Dengan Mediasi Komitmen Organisasi - Rizqul Anis; I Made Bayu Dirgantara; Meirani Harsasi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The performance of members of the police in the Traffic Unit of the Pekalongan Police is still not good, this is due to the low emotional intelligence of the members and the lack of attention from the leadership on the work environment, as well as the low organizational commitment of the members. The purpose of this study was to examine the effect of emotional intelligence, work environment and organizational commitment on member performance. This research was conducted by the Pekalongan Police Traffic Unit with a population of 67 people. The sample used is as many as 65 respondents. The independent variables in this study are emotional intelligence and work environment, while the dependent variable is the performance of members mediated by organizational commitment. Measurement of variables using a Likert scale. Data analysis using regression analysis. The software used for regression analysis is SPSS 25. The effect of Emotional Intelligence (X1) and Work Environment (X2) variables on Organizational Commitment (Y) can be made with the equation Y = 0.255X1 + 0.233X2. the indirect effect of Organizational Commitment (Y) as a mediator of Member Performance (Z) with the equation. Z = 0.272X1 + 0.244X2 + 0.263Y. The results of the analysis show that partially emotional intelligence and work environment have a positive and significant effect on organizational commitment. Partially emotional intelligence, work environment and organizational commitment have a positive and significant effect on member performance. Organizational commitment partially mediates the effect of emotional intelligence and work environment on member performance.